Avaliação da segurança e atividade gastrintestinal do extrato da infusão das folhas de Copaifera malmei Harms, em modelos experimentais in vivo e in vitro - Pavan, Eduarda (2017)
Copaifera malmei Harms, Fabaceae, is a plant native and endemic to the Brazilian Cerrado, whose leaf infusion is popularly used for the treatment of gastric ulcers and inflammatory diseases. This work aimed to evaluate the safety and activity upon gastrointestinal motility, intestinal secretion and inflammation of the standardized infusion extract of Copaifera malmei Harms leaves (SIECm) on in vivo and in vitro experimental models. SIECm was prepared by the infusion of Copaifera malmei leaves in hot water (40 g/L). SIECm genotoxicity (10, 30 or 100 µg/mL) was evaluated in Chinese hamster epithelial ovarian cells (CHO-k1) via comet and micronucleus assays. Subchronic toxicity was evaluated in Wistar rats by daily oral administration of SIECm (100, 400 or 1000 mg/kg) during 30 days, evaluating the following: behavioral changes, excretion of feces and urine, feed and water intake, weight gain, hematological and biochemical parameters, relative weight and histological analysis of vital organs. For the evaluation of SIECm activity (25, 100 and 400 mg/kg) on gastrointestinal motor function, gastric emptying and intestinal transit assays were carried out in Swiss mice, the effect of the extract on intestinal fluid accumulation via castor oil induced enteropooling assay in Wistar rats. The effect of SIECm on intestinal inflammation was evaluated by the trinitrobenzenesulfonic (TNBS) acid induced acute ulcerative colitis. SIECm did not cause genotxicity on the micronucleus assay. On the Comet Assay, pretreatment with SIECm prevented damage to DNA in all tested concentrations, while cotreatment reduced damage only on its lowest concentration. Post-treatment with the highest concentration of SIECm increased genetic damage induced by hydrogen peroxide. Oral administration of SIECm did not cause major alterations, except for the reduction of serum concentrations of AST and ALT at the dose of 100 mg/kg, triglycerides on the doses of 400 and 1000 mg/kg, and total leucocyte count and absolute number of lymphocytes at 1000 mg/kg. We also observed an increase in hematocrit and platelets on the blood of animals treated with 100 mg/kg of SIECm. Though statistically significant, these values are still within the physiological range for the species, with no histopathological alterations or clinical repercussions that indicate presence of a pathology. The extract reduced gastric emptying on the three tested doses, reduced intestinal transit at 100 and 400 mg/kg and reduced intestinal fluid buildup on the highest dose. On the TNBS induced ulcerative colitis assay, SIECm reduced inflammation at 24 and 400 mg/kg. The found results, attest to the oral safety of SIECm and point towards its application in situations of increased gastrointestinal motility and intestinal secretion.